A systematic review of optimal treatment strategies for localized Ewing's sarcoma of bone after neo-adjuvant chemotherapy. (March 2016) - Werier, Joel; Yao, Xiaomei; Caudrelier, Jean-Michel; Di Primio, Gina; Ghert, Michelle; Gupta, Abha A.; Kandel, Rita; Verma, Shailendra
Abstract: Objective: To perform a systematic review to investigate the optimal treatment strategy among the options of surgery alone, radiotherapy (RT) alone, and the combination of RT plus surgery in the management of localized Ewing's sarcoma of bone following neo-adjuvant chemotherapy. Methods: MEDLINE and EMBASE (1999 to February 2015), the Cochrane Library, and relevant conferences were searched. Results: Two systematic reviews and eight full texts met the pre-planned study selection criteria. When RT was compared with surgery, a meta-analysis combining two papers showed that surgery resulted in a higher event-free survival (EFS) than RT in any location (HR = 1.50, 95% CI 1.12–2.00; p = 0.007). However another paper did not find a statistically significant difference in patients with pelvic disease, and no papers identified a significant difference in overall survival. When surgery plus RT was compared with surgery alone, a meta-analysis did not demonstrate a statistically significant difference for EFS between the two groups (HR = 1.21, 95% CI 0.90–1.63). Both surgical morbidities and radiation toxicities were reported. Conclusions: The existing evidence is based on very low aggregate quality as assessed by the GRADE approach. In patients with localized Ewing's sarcoma, either surgery alone (if complete surgical excision with clear margin can be achieved) or RT alone may be a reasonable treatment option. The optimal local treatment for an individual patient should be decided through consideration of patient characteristics, the potential benefit and harm of the treatment options, and patient preference. Highlights: A systematic review of optimal treatment strategies for localized Ewing's sarcoma. Surgery alone or RT alone may be a reasonable treatment option. Optimal Tx needs thinking patient characteristics, preference; balancing benefit, harm.